Permeability measurement and discovery of dissociation process of hydrate sediments - Shen, Pengfei; Li, Gang; Li, Bo; Li, Xiaosen; Liang, Yunpei; Lv, Qiunan (Journal of Natural Gas Science and Engineering, 2020)
The study on the permeability of methane hydrates in fine quartz sands contributes to the accurate prediction of gas/water production and can effectively express the characteristics of fluid migration. In this study, the water effective permeability (k(w)) of methane hydrates in three fine quartz sands containing various hydrate saturation (S-H) were carried out under steady water injection and production. Experimental results indicated that the effect of particle sizes on k(w) was significant even though the difference in the average particle size of three fine quartz sands was relatively limited. The differential pressure of the hydrate sediments was completely recorded during permeability measurement, and the stabilization and decomposition process of hydrate could be clearly represented by differential pressure. The k(w) increased rapidly with the decomposition of hydrate and the appearance of flow channel in the hydrate sediments. Hydrate dissociation process was recorded in situ by Cold Field Emission Scanning Electron Microscopy (CFE-SEM), the dissociation of hydrates in pore space was clearly visible, and the hydrates in pore space were first dissociated into many small regions. A new reduction model between water relative permeability (k(rw)) and S-H was proposed on the basis of experimental results, and the experimental data fitted well with hydrates occupying pore centers. The effect of particle sizes on k(rw) was eliminated, the Archie saturation exponent n tended to increase with the increase of S-H, and n was recommended between 20 and 30.